Information system: analisis esensi, komponen, dan relevansinya dalam konteks ilmu perpustakaan - Soliha, Silfana Wiwit; Kusumaningtyas, Juwita Artanti (Librarium: Library and Information Science Journal, 2024)
Introduction. Library information systems, as formal socio-technical elements, are crucial in addressing collection management challenges and meeting information retrieval needs. This research makes an important contribution to the development of information systems according to library needs, addressing the issue of technology integration, and understanding the impact, benefits and challenges of implementation. Data Collection Methods. Using literature analysis, this research collected data from sources such as journals, books and articles. The data was systematically analyzed using content analysis techniques to develop a strong theoretical foundation and support the development of more in-depth research. Data Analysis. Data analysis in this study was conducted using content analysis techniques. This method involves collecting data from various literature sources, such as scientific journals, books, articles, and other documents. The data obtained was then systematically analyzed to develop a strong theoretical foundation, identify the strengths and weaknesses of previous research, and support the development of more in-depth and comprehensive research. Results and Discussion. Highlighting the crucial role of information systems in various contexts, this research uncovers the efficiency and innovation facilitated by information systems. Although faced with implementation challenges such as limited funding and technical skills, there are opportunities to improve the efficiency and effectiveness of library services by utilizing appropriate information technology and integrated system development. Conclusion. This research emphasizes the important role of information systems in improving the efficiency of information management and library services. Although faced with challenges, optimizing the implementation of information systems, such as Information Retrieval (IR), Digital Asset Management Systems (DAMS), Online Public Access Catalog (OPAC), and Collection Management Systems (CMS), can improve library performance. Suggestions for future research include exploring integration with new technologies, analyzing social and cultural impacts, and developing training models for librarians to deepen their understanding and contribution to information system development. Abstrak Pendahuluan. Sistem informasi perpustakaan, sebagai elemen sosio-teknis formal, krusial dalam mengatasi tantangan pengelolaan koleksi dan memenuhi kebutuhan pencarian informasi. Penelitian ini memberikan kontribusi penting pada pengembangan sistem informasi sesuai kebutuhan perpustakaan, menjawab isu integrasi teknologi, dan memahami dampak, manfaat, serta tantangan implementasinya. Metode penelitian. Dengan menggunakan analisis literatur, penelitian ini mengumpulkan data dari sumber-sumber seperti jurnal, buku, dan artikel. Data dianalisis secara sistematis dengan teknik analisis isi untuk menyusun landasan teori kuat dan mendukung pengembangan penelitian lebih mendalam. Data analisis. Analisis data dalam penelitian ini dilakukan dengan menggunakan teknik analisis isi (content analysis). Metode ini melibatkan pengumpulan data dari berbagai sumber literatur, seperti jurnal ilmiah, buku, artikel, dan dokumen lainnya. Data yang diperoleh kemudian dianalisis secara sistematis untuk menyusun landasan teori yang kuat, mengidentifikasi kelebihan dan kelemahan dari penelitian terdahulu, serta mendukung pengembangan penelitian yang lebih mendalam dan komprehensif. Hasil dan Pembahasan. Menyoroti peran krusial sistem informasi dalam berbagai konteks, penelitian ini mengungkap efisiensi dan inovasi yang difasilitasi oleh sistem informasi. Meskipun dihadapkan pada tantangan implementasi seperti keterbatasan dana dan keterampilan teknis, terdapat peluang untuk meningkatkan efisiensi dan efektivitas layanan perpustakaan dengan memanfaatkan teknologi informasi yang tepat dan pengembangan sistem yang terintegrasi. Kesimpulan dan Saran. Penelitian ini menegaskan peran penting sistem informasi dalam meningkatkan efisiensi pengelolaan informasi dan layanan perpustakaan. Meski dihadapkan pada tantangan, optimalisasi implementasi sistem informasi, seperti Information Retrieval (IR), Digital Asset Management Systems (DAMS), Online Public Access Catalog (OPAC), dan Collection Management Systems (CMS), mampu meningkatkan kinerja perpustakaan. Saran untuk penelitian mendatang mencakup eksplorasi integrasi dengan teknologi baru, analisis dampak sosial dan budaya, serta pengembangan model pelatihan untuk pustakawan guna memperdalam pemahaman dan kontribusi terhadap pengembangan sistem informasi.